Pelatihan Penulisan Artikel Ilmiah Bagi Guru di SMAN 1 Tanjung Sakti PUMU Kabupaten Lahat - Muhsana El Cintami Lanos; Hikmah Lestari; Agung Mahendra; Endie Riyoko; Tri Bayu Norito; Jujur Gunawan Manullang; Ardo Okilanda (Universitas PGRI Palembang, 2022)
This training aims for teachers to be able to compose scientific papers, conduct citations and can increase teachers' awareness and understanding of the importance of writing scientific papers. The method of implementing activities in the form of training, workshops, mentoring, practicum and evaluation as well as follow-up. While the activities were carried out at SMA N 1 Tanjung Sakti Pumu, Lahat Regency. The target of this training is teachers at SMA N 1 Tanjung Sakti Pumu, Lahat Regency, which consists of 50 participants. The results of this training are increasing knowledge and being able to write scientific papers independently, increasing teacher awareness and understanding of the importance of writing scientific papers. Writing scientific papers appropriately and according to standards will certainly be able to improve teacher assessment and quality.